2006
DOI: 10.1086/499308
|View full text |Cite
|
Sign up to set email alerts
|

Cataclysmic Variables from Sloan Digital Sky Survey. V. The Fifth Year (2004)

Abstract: This paper identifies the cataclysmic variables that appear in spectra obtained in 2004 as part of the Sloan Digital Sky Survey. Spectra of 41 objects, including seven systems that were previously known (CC Cnc, DW Cnc, PQ Gem, AR UMa, AN UMa, RX J1131.3+4322, and UMa 6) and 34 new cataclysmic variables are presented. The positions and ugriz photometry of all 41 systems are given, as well as additional follow-up spectroscopic, photometric, and/or polarimetric observations of eight of the new systems. The new o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
105
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(120 citation statements)
references
References 31 publications
15
105
0
Order By: Relevance
“…Aviles et al (2010) included SDSS J123813.73-033933.0 (hereafter SDSS1238) in the list of bounce-back CVs using a direct IR broad band photometry of the secondary and modeling the spectral energy distribution of the system. The subject of this paper is SDSS J080434.20+510349.2 (hereafter SDSS0804), which has a very peculiar light curve (Szkody et al 2006). A similar light curve has only been observed in one other system of SDSS1238.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…Aviles et al (2010) included SDSS J123813.73-033933.0 (hereafter SDSS1238) in the list of bounce-back CVs using a direct IR broad band photometry of the secondary and modeling the spectral energy distribution of the system. The subject of this paper is SDSS J080434.20+510349.2 (hereafter SDSS0804), which has a very peculiar light curve (Szkody et al 2006). A similar light curve has only been observed in one other system of SDSS1238.…”
Section: Introductionmentioning
confidence: 76%
“…1. Before the March 2006 superoutburst the brightness of the system was V ∼ 17.9 and the object displayed SDSS1238-like long-term variability (Szkody et al 2006;Zharikov et al 2006Zharikov et al , 2008. On March 4, 2006, a superoutburst commenced, exhibiting all attributes of WZ Sge-type: a large amplitude >6 mag, superhumps, and 11 echoes (Pavlenko et al 2006).…”
Section: Light Curve Variabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…We observed SDSS J0743 (Szkody et al 2006) on the night of 2009/01/23, for 2 h then another 1 h after a gap of 2 h. The light curve shows nothing out of the ordinary. One outburst has been seen for this CV in 2006 October, by the CSS (Drake et al 2009), where it increased in brightness by at least 5 mag.…”
Section: Five Sdss Cataclysmic Variables Showing No Periodic Brightnementioning
confidence: 87%
“…Szkody et al (2002Szkody et al ( , 2003Szkody et al ( , 2004Szkody et al ( , 2005Szkody et al ( , 2006Szkody et al ( , 2007Szkody et al ( , 2009Szkody et al ( , 2011) produced a catalogue of 285 CVs identified in this way. The Quasar Survey is estimated to be 95 per cent complete down to i < 19.1 (Vanden Berk et al 2005;Richards et al 2006).…”
Section: The Sdss CV Samplementioning
confidence: 99%